Overcoming America's infrastructure deficit: A fiscally responsible plan for public capital investment - S. Jay Levy; Walter M. Cadette (Levy Economics Institute of Bard College, 1998)
Condemned bridges, dilapidated school buildings, contaminated water supplies, and other infrastructure shortcomings threaten American growth, productivity, and prosperity. The authors of this brief propose a plan for financing infrastructure projects that is designed to have minimal effect on the federal budget and to promote sound fiscal operation. Federal zero-interest mortgage loans to state and local governments for capital projects specified by Congress can cut the cost of such projects, achieve needed improvements in the nation's infrastructure, and thereby contribute to the American economy's future.
Keywords: 330